2016
DOI: 10.1177/1524839916671301
|View full text |Cite
|
Sign up to set email alerts
|

The EDIC Method: An Engaging and Comprehensive Approach for Creating Health Department Workforce Development Plans

Abstract: In 2013, the Nebraska Department of Health & Human Services, Division of Public Health (Nebraska's State Health Department); and the University of Nebraska Medical Center, College of Public Health developed a comprehensive approach to assess workforce training needs. This article outlines the method used to assess the education and training needs of Division staff, and develop comprehensive workforce development plans to address those needs. The EDIC method (Engage, Develop, Identify, and Create) includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…As an entire department, LLCHD had training needs in only the financial planning and management (importance-capacity difference, 15 percentage points) and the policy development and program planning (19 percentage points) domains (Table 2). When 9 The tool was a survey that contained 130 questions and was administered by using SurveyMonkey.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As an entire department, LLCHD had training needs in only the financial planning and management (importance-capacity difference, 15 percentage points) and the policy development and program planning (19 percentage points) domains (Table 2). When 9 The tool was a survey that contained 130 questions and was administered by using SurveyMonkey.…”
Section: Resultsmentioning
confidence: 99%
“…Previous education and training assessments have fallen short for the following reasons: They have been conducted only in state health departments, they have lumped state and local health departments together, they have provided results only at the level of domains (and not the individual skill level), or they have been used to offer onesize-fits-all solutions. [5][6][7][8][9][10] However, we found that the gaps and training needs determined for LLCHD as a whole or for The needs assessment tool (a survey) was initially developed by Grimm et al 9 to assess education and training needs of local and state health department staff members. 9 The survey contained 130 questions and was administered by using SurveyMonkey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations